The ISA 1960: relevancy to the present situation in Malaysia / Nurhasyimah Nawawi, Nurul Shafika Zainal Abidin and Norhidayu Arshad - Nawawi, Nurhasyimah; Zainal Abidin, Nurul Shafika; Arshad, Norhidayu (2009)
In 1960, preventive detention law was placed on permanent footing with the enactment of Internal Security Act 1960 (ISA) which aimed in combating communists. The Act gives the Executive a very wide power to detain any person if he satisfies that it is necessary to prevent the person from acting in any manner prejudicial to the security of Malaysia. The problem arises when the Executive still uses the Act to detain a person who is not a communist. Due to this, the researchers aim to identify the extent of the Executive's power under ISA and to determine whether it is a valid exercise of power by the Executive and most importantly whether ISA is still relevant in Malaysia. Different background of interviewees has been obtained in order to make a balance report. The authorities are an officer from the Prime Minister Department, a police officer, academician and a representative from a Non-Governmental Organization. A comparison of application of Prevention Act has been made to observe the significance of ISA. Based on the result, it is suggested that ISA is relevant to the present situation in Malaysia to safeguard the country.